KEPENTINGAN INDIA MENOLAK KERJASAMA ONE BELT ONE ROAD (OBOR) TIONGKOK PADA TAHUN 2017-2019 - Oci Khairani; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research aims to explain the concerns of India rejecting the cooperation of One Belt One Road (OBOR) of China. OBOR is China's foreign policy as a new silk route which was declared by President Xi Jinping in 2013. The Author  uses  the perspective of  neo-mercantilism,  foreign policy theory, and  the analysis system is the nation state. This research uses an explanatory qualitative, the data collection techniques by library research are derived from literature such as books, journals, thesis, official documents and visits to internet sites. The result of this research indicate that India rejected the OBOR cooperation because of external factors and internal factors. Internal factors include economic interests and political interests. India rejects OBOR cooperation in three international forums. First, India refused to attend and boycott 1st Belt and Road Forum (BRF) on May 14, 2017. Second, India refused to support OBOR at the Shanghai Cooperation Organisation (SCO) Summit on June 10, 2018. Third, India did not attend 2nd Belt and Road Forum on April 25-27 2019. Keywords: OBOR,  Foreign Policy, National Interests, Neo-mercantilism